Cikapundung Riverbank Revitalization as The Implementation of CSR and Propose Green Marketing Plan PT. Telkom - Mukti, Felisia Noviana; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
Telecommunication industry in Indonesia is one of industry with high growth and futuristic. In the era of digital world, telecommunication industry players vying to attract customers with sustainable innovation. Celuller products and service that increase quite rapidly, accounted for mostly revenue stream in telecommunication companies. PT. Telekomunikasi Indonesia or Telkom is an important and big player in Indonesia telecommunication industry. Telkom is a State-Owned Enterprise (SOE) company engaged in telecommunication industry. When compared to others two SOE companies in same field, Telkom has now changed its core business to TIME (Telecomunication Information Media & Edutainment) with branch offices throughout indonesia. Headquarters is located in Bandung city and become the business center of all activities. Referred to its GCG (Good Corporate Governance), Telkom made the triple bottom line strategy as main strategy to enlarge its share in national, regional even international market. The implementation elements of the environment, social and economic will be redeemable in one are revitalization model. Considering of Telkom headquarters location, Bandung is the pilot project city to improve company image. This good imaging led to sales and trust increases of consumers mbusiness activities. The focus of this paper is to give idea of triple bottom line strategy implementation through a CSR (Corporate Social Responsibility) model for marketing ‘tools’. The method used is green marketing plan approach because its same elements of triple bottom line. Some corporate strategy, CSR concept and green marketing recommendations will be proposed in this paper. New ideas generated in pilot project model of Cikapundung riverbank slums area revitalization which also an implementation of green marketing plan and triple bottom strategy of Telkom. However, in marketing activities implementation, the strategy has not yet become a conduct core of business activities. The focus of this paper is to give idea of triple bottom line strategy implementation through a CSR (Corporate Social Responsibility) model for marketing ‘tools’. The method used is green marketing plan approach because its same elements of triple bottom line.Keywords: telecommunication, green marketing, CSR, triple bottom line, revitalization and Cikapundung riverbank